2020
DOI: 10.1038/s41467-020-18554-x
|View full text |Cite|
|
Sign up to set email alerts
|

A Cu(II)–ATP complex efficiently catalyses enantioselective Diels–Alder reactions

Abstract: Natural biomolecules have been used extensively as chiral scaffolds that bind/surround metal complexes to achieve stereoselectivity in catalytic reactions. ATP is ubiquitously found in nature as an energy-storing molecule and can complex diverse metal cations. However, in biotic reactions ATP-metal complexes are thought to function mostly as co-substrates undergoing phosphoanhydride bond cleavage reactions rather than participating in catalytic mechanisms. Here, we report that a specific Cu(II)-ATP complex (Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 74 publications
5
27
0
Order By: Relevance
“…In a recent study of the same reaction catalyzed by Cu 2+ -adenosine triphosphate, density functional theory gas phase calculations suggested that Si-face attack was favored due to hydrogen bonding of (2) with phosphate oxygen atoms leading to a reduced energy barrier for the cycloaddition. 44 One possible explanation for our system is that DNA-(2) interactions in the pocket created between the Si-face of 1(a) and dsDNA lead to a free energy transition state reduction causing the observed rate increase and high ee observed experimentally for "21-10, 11". An alternative explanation for the observed ee, is that the relevant configuration for catalysis is with (1a) oriented as shown in Figure S26, i.e., with (1a) rotated by 180 o compared to its configuration in Figures 2g, 2h.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…In a recent study of the same reaction catalyzed by Cu 2+ -adenosine triphosphate, density functional theory gas phase calculations suggested that Si-face attack was favored due to hydrogen bonding of (2) with phosphate oxygen atoms leading to a reduced energy barrier for the cycloaddition. 44 One possible explanation for our system is that DNA-(2) interactions in the pocket created between the Si-face of 1(a) and dsDNA lead to a free energy transition state reduction causing the observed rate increase and high ee observed experimentally for "21-10, 11". An alternative explanation for the observed ee, is that the relevant configuration for catalysis is with (1a) oriented as shown in Figure S26, i.e., with (1a) rotated by 180 o compared to its configuration in Figures 2g, 2h.…”
Section: Resultsmentioning
confidence: 83%
“…31,32 The ability for enantioselectivity by the DNA-ArM catalyst is determined by the enantiomeric excess (ee%) of the Si-endo versus Re-endo. 3 4,4'-dimethyl-2,2'bipyridine (dmbipy) was selected as the achiral ligand to bridge the Cu(II) catalytic center and the dsDNA scaffold. 33 We include for comparison the performance of the natural salmon testes DNA (st-DNA) and a G•C-rich dsDNA sequence composed of the 21 nucleotide G-rich human telomeric sequence HT21.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 The ability for enantioselectivity by the DNA-ArM catalyst is determined by the enantiomeric excess (ee%) of the Si-endo versus Re-endo. 3 4,4'-dimethyl-2,2'bipyridine (dmbipy) was selected as the achiral ligand to bridge the Cu(II) catalytic center and the dsDNA scaffold. 33 We include for comparison the performance of the natural salmon testes DNA (st-DNA) and a G•C-rich dsDNA sequence composed of the 21 nucleotide G-rich human telomeric sequence HT21.…”
Section: Resultsmentioning
confidence: 99%
“…Artificial metalloenzymes (ArMs) can combine the chiral environment of biomolecular scaffolds with the catalytic properties of a transition metal. [1][2][3][4][5][6] Since the introduction of DNA-based ArMs in 2005, 7 enantioselective catalysis by metal ions or metal ion complexes assembled on a DNA scaffold has been demonstrated for Diels-Alder, [7][8][9][10][11][12][13] Friedel-Crafts alkylation, [14][15][16][17][18] Michael addition, [19][20][21][22] and other reactions. [23][24][25][26][27][28][29][30] Despite progress in correlating the catalytic performance of DNA-ArMs with their DNA sequence, 8-12, 15-18, 21, 24-28, 30 pinpointing which of the many possible chiral microenvironments created by the interaction between the DNA and the bound metal, or metal complex, is responsible for enantioselective catalysis, remains elusive.…”
Section: Introductionmentioning
confidence: 99%